Boganmeldelser - Elisabeth Rynning; Peter Gottlieb; Kjersti Ericsson; M. Gregersen; Frieder Dünkel; Heidi Mork Andersen; Alexander Carnera Ljungstrøm; Kristin Skjørsten (Nordisk Tidsskrift for Kriminalvidenskab)
Book reviews